Creative Methods in Sociocultural Community Development to Further the Participation of Citizen Groups in Decision-Making Processes - Stade, Peter; Wandeler, Bernard (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2011)
The article focuses on learnings based on three cases of participation in decision-making processes involving students in social work in the context of the Swiss democratic life particularly opened to this kind of initiative. Perceived as an important base for sustainable development, participation has to lean on basic conditions, such as shared powers and responsibility of the process. Time and use of creative methods are also essential for success. Observations confirm that participants in this kind of process benefit directly from it, in particular regarding gain of autonomy and development of sense of belonging to a social group and a given territory, but also find there base of a wider social participation in the future.